Implicações da performatividade na formação continuada e no trabalho pedagógico do gestor escolar - Corrêa, Francinete Massulo (2017)
The present study has as problematic the formative process continued of managers of public basic education. In recent years, is part of the discussions about the reorientation of education vocational training school managers, academic and practical aspects of work, with a view to adapting these to the demands of the processes of organization and management of public school. In this attempt, was created the National School Program managers of Public basic education (PNEGEBP). Analyze the relationship between the formation of school graduates of the course managers of Lato Sensu graduate studies in school management and its implications for the pedagogical work in front of the building of a new professionalism in the management of the public school in the city of Manaus's general objective of this study. The empirical research had as locus three schools located in the metropolitan area of this city, which have managers course graduates of lato courses offered by the Federal University of Amazonas. To that end, it was necessary to carry out study on recent educational reforms and public policies of continuing training, designed to meet the legal requirements and the need for particular school managers profile for new management model from school. To analyse the modalities of professional managers, ID consider the processes of socialization by which professional identities are constructed and if rebuilding and how articulate front crises experienced in everyday working practice in the development of the new roles that take account of the demands of performance and productivity. The theoretical framework formed by the articulation of two categories: performativity and identity, with main focus on first from the works of Stephen Ball and Claude Dubar.. The research of qualitative nature, with exploratory character, considered the policy cycle approach (policy cycle approach), as Ball and Associates, which provides the contexts of influence, text production and practice. Privileged the practical context for considering that the central objective of research is to the continued training of managers to meet the demands of daily life of the school. The empirical data were collected through semi-structured interviews. We used the technique of content Analysis, considering the theme as the unit of analysis for organization and interpretation of the answers of the interviewees. The results revealed the potential of pedagogical course proposal as an opportunity for reflection on the practices, in order to respond to the demands of planning and execution of the work in the everyday life of the school. At the same time, it was observed that in the everyday life of the school, provided for by the need to fulfill goals and results, if managers are increasingly performing rules and have reduced their concrete possibilities of conducting critical reflections about their own work processes in the management of the school and deny their identity of autonomous people in benefit of the identity of the school. It was concluded that the subject of this formative process should seek, in the context of practice, together with other subjects, to facilitate the connection with policymakers and other social institutions, in the quest for fulfillment of emancipatory continuing education.